2012
DOI: 10.1901/jaba.2012.45-539
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Question “What Is This?” on Tact‐training Outcomes of Children With Autism

Abstract: Tact training is a common element of many habilitative programs for individuals with developmental disabilities. A commonly recommended practice is to include a supplemental question (e.g., "What is this?") during training trials for tacts of objects. However, the supplemental question is not a defining feature of the tact relation, and prior research suggests that its inclusion might sometimes impede tact acquisition. The present study compared tact training with and without the supplemental question in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…The current study replicated general tact training procedures conducive to acquisition in children with ASD when using visual training stimuli (e.g., Leaf et al, ; Majdalany et al, ; Marchese et al, ; Schnell et al, ) and extended the successful use of these procedures in tacts of novel sensory modalities (Dass et al, ) by targeting auditory stimuli. The comparison of teaching arrangements (i.e., isolated and compound conditions) suggests the need for repeated evaluations.…”
Section: Discussionsupporting
confidence: 69%
“…The current study replicated general tact training procedures conducive to acquisition in children with ASD when using visual training stimuli (e.g., Leaf et al, ; Majdalany et al, ; Marchese et al, ; Schnell et al, ) and extended the successful use of these procedures in tacts of novel sensory modalities (Dass et al, ) by targeting auditory stimuli. The comparison of teaching arrangements (i.e., isolated and compound conditions) suggests the need for repeated evaluations.…”
Section: Discussionsupporting
confidence: 69%
“…If a verbal stimulus occurs in conjunction with the nonverbal stimulus, it is likely that the response is under multiple control (Michael, Palmer, & Sundberg, ). Marchese, Carr, LeBlanc, Rosati, and Conroy () evaluated the effects of verbal antecedent stimuli on the acquisition of tacts by children with ASD. Results indicated that inclusion of the verbal antecedent stimuli did not hinder tact acquisition or maintenance of the tacts under conditions in which the verbal antecedent stimuli were absent.…”
Section: Discussionmentioning
confidence: 99%
“…The present data add empirical support for Skinner's (1957) conceptualization of human language, as well as some initial yet limited utility of the PEAK curriculum (Dixon, 2014b) to teach verbal behavior to persons with autism. Prior research has recently documented technologies in which clinicians can teach ever more complex verbal operants such as generalized mands (Falcomata, Wacker, Ringdahl, Vinquist, & Dutt, 2013), mand relations (Betz et al, 2011), informational mands (Lechago, Howell, Caccavale, & Peterson, 2013;Shillingsburg, Bowen, Valentino, & Pierce, 2014), tacts (Marchese, Carr, LeBlanc, Rosati, & Conroy, 2012), novel intraverbals and dictation (Greer, Yuan, & Gautreaux, 2005), and cross-operant transfers of responding (Ingvarsson, Cammilleri, & Macias, 2012;Kooistra, Buchmeier, & Klatt, 2012;May, Hawkins, & Dymond, 2013;Miguel & Kobari-Wright, 2013). In an era of continued criticism that behavioral interpretations of language are inadequate for explaining complex language, it appears that subsequent investigations that explore the extensive opportunities that Skinner's analysis affords our field will weaken the position of disbelief.…”
Section: Discussionmentioning
confidence: 99%